The Symbolic Meaning of the Sekujang Dance in Relation to Customary Law Values and Local Cultural Development in Seluma - Rocky Eric Prianto; Natasya Ramadhani; Daffa Nouvalmuarif; M Akbar Farreldy; Ferdian Al Hasyimi (The Future of Education Journal, 2026)
The Sekujang Dance is a cultural heritage of the Serawai people in Bengkulu, particularly in Seluma Regency. This dance serves not only as entertainment but also has symbolic meaning closely linked to local traditional values ​​and beliefs. This study aims to determine the symbolic meaning of the Sekujang Dance in relation to customary law and its role in the development of local culture. The method used in this study is a qualitative approach, examining the cultural values ​​and traditions embodied in the Sekujang ritual. The results indicate that the Sekujang Dance contains various symbols that reflect respect for the spirits of those who have died unnaturally and serve as a medium for preserving the traditional values ​​of the Serawai people. Therefore, the Sekujang Dance plays a crucial role in maintaining customary law and strengthening local cultural identity.